Fazer a louca: práticas editoriais, discursivas e poéticas na montagem da eulouca - Otávio Campos Vasconcelos Fajardo (2022)
Taking Foucault's statement that madness is an excluded language as a reference, what happens when we are faced today with a poetics that asserts itself as covered by the veil of mental illness? If the processes of exclusion of certain bodies occur in language, barring its excesses, we propose thinking from the inside out. How to think of a poetics that is based on the excessive use of languages and their means? What is possible in the language that takes place from the ambiguous place of mental illness? These are the questions that lead us to the works of two contemporary poets: Cláudia R. Sampaio and Carla Diacov. Being the first Portuguese and the second Brazilian, their poetic works come closer not only by language, but also by the spectrum of madness that erupts both in their lives and in their artistic productions. The “I” in poems, therefore, has a double inscription: it builds the image of the mad poet at the same time that it makes madness vibrate textually in the works. Such a particle, called madme, is what we intend to investigate. In addition to being a double inscription, another characteristic of madme is that it is feminine, regardless of the gender of the person who produces it, which is why it is relevant to make use of studies on the feminine in language, such as those proposed by Branco (1994) and Lacan (1985) to think of this language that destabilizes the order and finds itself further, as an jouissance beyond. For this reason, we also propose discussions that involves the editing processes of these poets in books, starting from the idea that the book is an order established within the author's discourse, as Chartier defends in The Order of Books (1998). It is in this (self) critical tension that we think about the materialization of discourses in books, as well as dealing with the spectacular evidence and political-affective ambiguities that are established in the relationship between madness, mental illness and montage.